2021
DOI: 10.1007/s00586-021-06774-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the implant performance of magnetically controlled growing spine rods: a review article

Abstract: Purpose Early-Onset Scoliosis (EOS) (defined as a curvature of the spine ≥ 10° with onset before 10 years of age) if not properly treated, can lead to increased morbidity and mortality. Traditionally Growing Rods (TGRs), implants fixated to the spine and extended every 6–8 months by surgery, are considered the gold standard, but Magnetically Controlled Growing Rods (MCGRs) avoid multiple surgeries. While the potential benefit of outpatient distraction procedure with MCGR is huge, concerns still r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…By combining the limited information provided by the manufacturer (Nuvasive Inc.) with the literature 13 , 14 , it is possible to outline the construction of the MCGR, the lengthening mechanism, and the interaction between ERC and MCGR: An internal dipolar magnet mounted on a screw mechanism is brought into rotation, which leads to an extension of the rod that drives the distraction. The rotation is initiated by an interaction with an external rotating magnetic field generated by the ERC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining the limited information provided by the manufacturer (Nuvasive Inc.) with the literature 13 , 14 , it is possible to outline the construction of the MCGR, the lengthening mechanism, and the interaction between ERC and MCGR: An internal dipolar magnet mounted on a screw mechanism is brought into rotation, which leads to an extension of the rod that drives the distraction. The rotation is initiated by an interaction with an external rotating magnetic field generated by the ERC.…”
Section: Introductionmentioning
confidence: 99%
“…A large multicentre study comparing MCGR with TGR reported improvements in quality-of-life measures and concluded that the reduced number of surgeries lessens the psychosocial burden 7 . However, an increasing number of MCGR failure mechanisms have been observed [8][9][10][11] , and approximately 10% of patients undergo unplanned revisions 12 most often because of anchor failure, failure of the distraction mechanism 13,14 , fracture of the internal magnet 15 or a non-functioning MCGR 16 . Titanium wear has raised concerns 17 .…”
mentioning
confidence: 99%
“… 2 The aim of these systems is to control curve progression while allowing for spinal growth until the patient has reached their full development potential. 3 Traditional growing rods (TGRs) are constructs fixed to the spine using pedicle screws or hooks that are surgically lengthened every 6 to 8 months. Magnetically controlled growing rods (MCGRs), in contrast, do not need repeated rod distraction surgeries performed when a TGR is implanted, thanks to a magnetic distraction mechanism, which allows for outpatient lengthening procedures.…”
mentioning
confidence: 99%
“…Distraction-based systems are usually used to surgically treat the most severe cases 2. The aim of these systems is to control curve progression while allowing for spinal growth until the patient has reached their full development potential 3. Traditional growing rods (TGRs) are constructs fixed to the spine using pedicle screws or hooks that are surgically lengthened every 6 to 8 months.…”
mentioning
confidence: 99%
“…D ifferent approaches exist in treating EOS depending on its severity and the age of the patient, including observation, casting, and bracing or surgical treatments involving spine implants and fusion of vertebrae. [1][2][3][4] Magnetically controlled growing rods (MCGRs) have been used for the treatment of EOS, requiring elongation every 3 months through an external controller without open surgery, unlike traditional growing rods which need manual lengthening through repeat operations. 5 The only widely commercially available MCGR has been the MAGEC rod (Magnetic Expansion Control, NuVasive Specialised Orthopaedics, San Diego, USA).…”
mentioning
confidence: 99%